Experiences between philosophy and communication : engaging the philosophical contributions of Calvin O. Schrag - Ramsey, Ramsey Eric, 1960-; Miller, David James, 1957- (SUNY series in the philosophy of the social sciences., 2003)
"Providing developments and advancements concerning the thought of Calvin O. Schrag, this book includes the first full-length interview with the American continental philosopher and covers his long and illustrative philosophical contribution to thinking about the consequences of communication. The influence of Schrag's work is significant and broad, and these nine thought-provoking pieces by leading scholars whose work has been influenced by his philosophy presents the best contemporary thought on communicative praxis. Encompassing questions of democracy, the public and private spheres, and relations inside organizational structures, to questions of giving and ethics, rhetoric and narrative, suffering and love, this is a wellspring of insight and provocation for both those already familiar with Schrag's work and those seeking a keen invitation to his many critical reflections."--Jacket